2015
DOI: 10.15761/ifnm.1000127
|View full text |Cite
|
Sign up to set email alerts
|

Iron sequestration is not the main mechanism in the inhibition of Staphylococcus aureus growth by cranberry phytochemicals

Abstract: Some edible berries such as cranberry have been shown to process antimicrobial activity. One of the antimicrobial actions is hypothesized to be sequestration of iron required for bacterial growth as berry phytochemicals contain strong iron binding groups. Cranberry phytochemicals obtained by solid phase extracts (SPE) from a commercial cranberry juice were studied for their inhibition of Staphylococcus aureus. At 100 µg gallic acid equivalents/mL of phenolic materials, cranberry SPE inhibited bacteria growth b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Intestinal dysfunction with increased permeability and downregulated tight junctions plays an important role in the pathogenesis of IBD and other inflammatory diseases [ 19 , 20 ]. In this study, we found that DSS increased permeability (serum LPS) and downregulated tight junctions expression, while genistein markedly alleviated DSS-induced colonic dysfunction in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal dysfunction with increased permeability and downregulated tight junctions plays an important role in the pathogenesis of IBD and other inflammatory diseases [ 19 , 20 ]. In this study, we found that DSS increased permeability (serum LPS) and downregulated tight junctions expression, while genistein markedly alleviated DSS-induced colonic dysfunction in mice.…”
Section: Discussionmentioning
confidence: 99%
“…11,28 While the mechanism of action of EDTA against Gram-positive bacteria remains poorly understood, studies suggest the target site for EDTA activity may be intracellular or EDTA potentially chelates ions required for biological processes essential for bacterial growth and survival. 12,13,21,29…”
Section: Resultsmentioning
confidence: 99%
“…11,28 While the mechanism of action of EDTA against Gram-positive bacteria remains poorly understood, studies suggest the target site for EDTA activity may be intracellular or EDTA potentially chelates ions required for biological processes essential for bacterial growth and survival. 12,13,21,29 The lack of bactericidal activity observed with 7.63 mM tEDTA was due to the absence of sufficient free tEDTA molecules to interact with the bacteria and exert an antimicrobial effect. While the higher concentration of 28 mM tEDTA provided excess molecules for bacterial interaction, this was not sufficient for bactericidal activity against the challenge uropathogens, as dened by a $3 log 10 reduction in bacterial density aer 24 h exposure to tEDTA relative to the starting inoculum.…”
Section: Resultsmentioning
confidence: 99%
“…Quercetin and myricetin, the two most abundant components in our flavonoid fraction, are well known for their bivalent metal cations chelation. Due to the presence of ortho dihydroxyl phenolic and hydroxyketo groups, these flavonols can chelate “free” copper and iron ions from the environment, which could be the reason for the increased growth inhibition by CRFp85 [34].…”
Section: Discussionmentioning
confidence: 99%